Detection of Breast Lumps with Fine Needle Aspiration Cytology: Experience of 50 Cases in Bangladesh - Quddus, Md Abdul; Jahan, Nusrat; Syeed-Ul-Alam, SM; Jahan, Semonty; Moureen, Adneen (Journal of Current and Advance Medical Research, 2024)
Background: Detection of breast lump is very crucial. Objective: This study was carried out to evaluate the effectiveness of FNAC as a diagnostic method for breast lump. Methodology: This cross sectional study was conducted among 50 women with breast lump at Popular Medical College Hospital, Dhaka, Dhaka Medical College Hospital and Ad-Din Barrister Rafique Ul Huq Hospital, Dhaka during the period of November 2021 to April 2022. This study was conducted using convenient type of non-probability sampling technique. Data were collected by face to face interview, clinical examination and findings of both cytological and histopathological examination. Results: The study revealed the most benign breast lesion (89.45%) were below the age of 40 years and most of the breast cancer (91.2%) were above the age of 40 years. The study showed that 29 cases (58.0%) were diagnosed as benign clinically but cytologically 30(60.0%) cases were benign. Clinically 14(27.0%) cases were malignant but cytologically 13(26.0%) cases malignant. Clinical diagnosis of 8(7.5%) cases were uncertain, whereas cytologically 2(4.0%) cases were suspicious of malignancy and 1(2.0%) case was atypical. The comparison study between cyological and final histopathological diagnosis showed that out of 28 benign lesions diagnosed cytologically among which only 2 cases were found malignant histologically like false negative 2 (7.20%). 13 malignant cases were diagnosed cytologically which were confirmed histologically like no false positive was found. The study found that sensitivity of FNAC 85.3% of the presence of breast cancer and specificity 100.0% for absence of breast cancer. They also showed that the negative predictive value of FNAC for benign breast lump was 93.5% and positive predictive value for malignant breast lump was 100.0% and the overall diagnostic accuracy was 95.40%. Conclusion: In conclusion, FNAC can be used as a diagnostic method in the management of breast lump which has reasonable sensitivity and specificity. Journal of Current and Advance Medical Research, July 2023;10(2):65-69